Pelayanan Pemanduan dan Penundaan Kapal BSP XXV Melalui Sistem PHINNISI Oleh PT. Bahtera Kencana Djaya Lampung - Avendes Janaolo Finoawa; Dirhamsyah Dirhamsyah; Taruna Ginting (JURNAL RISET MANAJEMEN (JURMA), 2025)
Ship guiding and postponement services are one of the important aspects in ensuring safety and operational efficiency at the port. This research discusses the application of the PHINNISI (Port and Harbormaster Integrated Information System) system in the process of guiding and delaying BSP XXV ships. PHINNISI is an information technology-based system designed to improve coordination and supervision of ship operations at the port. Through real-time data integration and digitisation of procedures, the system enables more effective monitoring of vessel movements, arrival times, and delay processes. The purpose of writing this paper is to find out how the BSP XXV Ship Guidance and Delay Service through the Phinnisi System by PT Bahtera Kencana Djaya Lampung. The author collects data using two research methods, namely the library method (Library Research) and the field method (Field Research). The results of this study are the BSP XXV Ship Guiding and Delay Services through the Phinnisi System by PT Bahtera Kencana Djaya Lampung. Starting from entering the PHINNISI application through the site (phinnisi.Pelindo.co.id). Then the agent logs in using the company account that has been registered in the PHINNISI application, after logging in the agent makes a request for ship guiding and delaying services and makes payment, after obtaining permission from KSOP.